Linkage of national soil quality measurements to primary care medical records in England and Wales: a new resource for investigating environmental impacts on human health - Gibson, Jack E.; Ander, E. Louise; Cave, Mark; Bath-Hextall, Fiona; Musah, Anwar; Leonardi-Bee, Jo (BioMed Central, 2018)
Background: Long-term, low-level exposure to toxic elements in soil may be harmful to human health but large longitudinal cohort studies with sufficient follow-up time to study these effects are cost-prohibitive and impractical. Linkage of routinely collected medical outcome data to systematic surveys of soil quality may offer a viable alternative.